Inclusion of Tax Awareness in School Students in Teras Banten - Fara Fitriyani (MOVE: Journal of Community Service and Engagement, 2023)
Inclusion of tax awareness is education to the public regarding tax awareness that is integrated and internalized in a part of the media or other activities carried out by third parties, in this case universities. The Directorate General of Taxes with the Ministry of Education, Culture, Research and Technology as the party in charge of education seeks to in still tax awareness in students and teaching staff through the integration of tax awareness material in education. Tax education is carried out by conducting a tax awareness campaign by providing materials about tax awareness. Participants involved in this community service activity were school students in the Teras Village area, Serang Regency, Banten Province.